1994
DOI: 10.1523/jneurosci.14-05-03005.1994
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic glutamate receptor mRNA expression in the basal ganglia of the rat

Abstract: Metabotropic glutamate receptors (mGluRs) couple the actions of glutamate to intracellular second messenger systems through G-proteins. The mGluRs play an important role in the regulation of basal ganglia function. Ligand binding studies have revealed that the basal ganglia contain at least two pharmacological types of metabotropic binding sites. Agonists of mGluRs can affect both in vitro electrophysiologic responses of striatal neurons and motor behavior in vivo. Recently, cDNAs encoding five mGluRs have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
335
2
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 487 publications
(371 citation statements)
references
References 58 publications
30
335
2
1
Order By: Relevance
“…Adenosine A 2A receptor mRNA is highly expressed in the striatum, nucleus accumbens, olfactory tubercle, and the globus pallidus (Jarvis et al, 1989) where group I mGlu receptors (including subtypes 1 and 5) are also strongly expressed (Testa et al, 1994). In addition, group I mGlu receptors are present in the subthalamic nucleus (STN) and the substantia nigra pars reticulata (SNr) (Tallaksen-Greene et al, 1998;Testa et al, 1994).…”
Section: Functional Interaction Between a 2a And Mglu 5 Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adenosine A 2A receptor mRNA is highly expressed in the striatum, nucleus accumbens, olfactory tubercle, and the globus pallidus (Jarvis et al, 1989) where group I mGlu receptors (including subtypes 1 and 5) are also strongly expressed (Testa et al, 1994). In addition, group I mGlu receptors are present in the subthalamic nucleus (STN) and the substantia nigra pars reticulata (SNr) (Tallaksen-Greene et al, 1998;Testa et al, 1994).…”
Section: Functional Interaction Between a 2a And Mglu 5 Receptorsmentioning
confidence: 99%
“…In addition, group I mGlu receptors are present in the subthalamic nucleus (STN) and the substantia nigra pars reticulata (SNr) (Tallaksen-Greene et al, 1998;Testa et al, 1994). In the striatum, adenosine A 2A receptors are predominantly expressed by g-amino butyric acid (GABA)-enkephalin striatopallidal neurons, where they colocalize with DA D 2 receptors (Fink et al, 1992;MartinezMir et al, 1991) and are also present in 25% of cholinergic interneurons (Schiffmann et al, 1991;Fredholm et al, 2001).…”
Section: Functional Interaction Between a 2a And Mglu 5 Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Group II (mGluRs 2 and 3) and group III (mGluRs 4 -8) receptors inhibit adenylyl cyclase, although with different pharmacological profiles (for review, see Pin and Duvosin, 1995;Roberts, 1995). Ligand-binding studies have shown the striatum to possess a high density of mGluR binding sites (Albin et al, 1992), and several mGluR mRNAs and proteins are expressed by striatal neurons, including members of all three mGluR groups (Abe et al, 1992;Martin et al, 1992;Shigemoto et al, 1992Shigemoto et al, , 1993Fotuhi et al, 1993;Ohishi et al, 1993a,b;Saugstead et al, 1994;Testa et al, 1994;Joly et al, 1995;Romano et al, 1995).…”
Section: Abstract: Metabotropic Glutamate Receptor; Basal Ganglia; Smentioning
confidence: 99%
“…Upon binding glutamate, the receptors directly gate ion channels (ionotropic receptors) and/or change conformation (metabotropic receptors) to transmit electrical signals between neurons and regulate expression of targeted genes via second messengers. Each receptor subunit/subtype has a unique brain expression pattern indicative of different brain subdivisions or cell types having different glutamate receptor functions (Bahn et al, 1994;Conti et al, 1994;Standaert et al, 1994;Testa et al, 1994). Furthermore, some of these subunits/subtypes have different mRNA splice variants contributing further to the diversity of receptor function.…”
mentioning
confidence: 99%